Input Value Added Tax Refund Policy for Taxable Enterprise Experiencing Production Failures - Oktaria, Rut (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2012)
In their effort to amend the legislation of Value Added Tax (VAT), the government and the House of Representatives have amended the latest Law Number 8 of 1983 with Law Number 42 of 2009 pertaining to the third amendments of VAT on Goods and Services and Luxury Sales Tax (LST). Substantial changes, occurred in the policy of Input VAT refund for Taxable Enterprise experiencing production failures, is the focus of this research. This study aims to describe the background of the issuance of the Input VAT restitution refund policy for Taxable Enterprise experiencing production failure, and create inventory of the potential problems that may arise in relation to the issuance of the aforementioned policy. This study uses qualitative approach and library and field research as its data collection techniques. The result shows that there are incongruities among the Law, the general concept and the legal character of VAT. On the other hand, the regulation is amended to prevent any abuse on the mechanism of VAT restitution. The problems that may potentially arise from this new regulation are the issues related to the regulation consistency within the basic concept of VAT, and economic disincentives that can be experienced by Taxable Enterprises from certain industries. Therefore, at the macro level, this policy may hamper the growth of investment in Indonesia.